A 250 ka leaf-wax δD record from a loess section in Darai Kalon, Southern Tajikistan. (15th March 2019) - Häggi, Christoph; Eglinton, Timothy I.; Zech, Wolfgang; Sosin, Piotr; Zech, Roland
Abstract: The climate of SW Central Asia is influenced by strong precipitation seasonality with dry summers and winter-spring precipitation delivered by mid-latitude westerlies. Due to its geographic position, SW Central Asia is a key locality for identifying fluctuations of westerlies, Siberian High and SW monsoon. Yet, there is only limited information on the Pleistocene climate history in SW Central Asia. Here we use plant-wax biomarkers and their hydrogen isotope (δD) composition from a loess section in Darai Kalon, southern Tajikistan, to reconstruct environmental conditions of the past 250 thousand years (ka). We focus on the hydrogen isotope composition of long-chain n- alkanes (δDAlk ) and long-chain n- carboxylic acids (δDCarb ) to reconstruct changes in the hydrological system. Moreover, we infer information about past vegetation changes from proxies based on the relative abundance of these compounds. Results show that during glacials, grasses dominated whereas during interglacials arboreal species prevailed. These changes in vegetation follow the dominant glacial-interglacial variability visible in the loess stratigraphy. Our results are in line with decreased precipitation during glacials as a result of a more extensive Siberian High. Isotope measurements reveal a close relation of δDAlk and δDCarb with insolation, controlled by 20 ka cycles of orbital precession that is distinct from the glacial-interglacial variability of the loess stratigraphy. Depleted (enriched) δDAlk and δDCarb values coincide with low (high) winter-spring insolation. The precessional mode of our isotope records is likely influenced by variations in the precipitation seasonality between winter and spring precipitation caused by insolation-induced temperature changes. In comparison with speleothem records along the westerly path, our results further indicate that the winter westerly storm tracks did not extend to the east of the Tian Shan during the last two glacial cycles. Highlights: Climate and vegetation reconstruction from a Tajik loess section using plant-waxes. Strong glacial-interglacial variability of vegetation reconstructions. Insolation forcing of leaf-wax δD in Central Asia over the last 250 ka. Decoupling between local climate signals and reconstructed precipitation δD. Isotope signal influenced by variations in precipitation seasonality.